(untitled) (International Journal of Plant Biology, 2014)
Jatropha curcas L. is an important biofuel plant that can be regenerated in vitro using seeds. The fruits of J. curcas do not reach maturity at the same time although they are on the same bunch. This study was undertaken to evaluate the effect of seeds, from fruits at different stages of maturity, on in vitro plantlet formation. Callus was induced on Murashige and Skoog medium using different concentrations of 2,4 dichlorophenoxyacetic acid (2,4-D) and 6 benzylaminopurine (BAP). 2,4D at a concentration of 3.0 mg/L and BAP at 1.0 mg/L were found to be optimum for callus formation. In vitro plantlets obtained on BAP were smaller with thicker hypocotyl and thicker roots. On the other hand, seeds from mature fruits gave better results for in vitro plantlet regeneration on 1.0 mg/L BAP without any rooting medium. A combination of sand and soil were used for acclimatization. Best results were obtained when sand and soil were used in equal amounts. Results also showed that seed maturity is an important factor for in vitro plant regeneration of J. curcas and that root formation in vitro does not require additional plant growth regulator substance.